Correction: Nocini et al. Improving Nasal Protection for Preventing SARS-CoV-2 Infection. Biomedicines 2022, 10, 2966 - Riccardo Nocini; Brandon Michael Henry; Camilla Mattiuzzi; Giuseppe Lippi (Biomedicines, 2025)
In the original publication [...]